SAT0405 Risk of Status Epilepticus and Intractable Epilepsy in Systemic Lupus Erythematosus Patients with Antiphospholipid Antibodies. (9th June 2015) - Sheth, K.; Mehta, T.; Sheth, V.; Soni, R.; Puri, S.; Parke, A.L.
Abstract : Background: Antiphospholipid antibodies are present in 33% of patients with Systemic Lupus Erythematosus (SLE). Studies have shown that presence of antiphospholipid antibody independently increases seizure risk in SLE patients. In this nation-wide study, we tried to determine if antiphospholipid antibodies are independent predictors of intractable epilepsy and status epilepticus (general and partial). Objectives: To determine if antiphospholipid antibody is an independent predictor of status epilepticus, grand mal status epilepticus or epilepsia partialis continua in patients with SLE. Methods: We queried the Healthcare Cost and Utilization Project's (HCUP) Nationwide Inpatient Sample (NIS) between 2002 and 2011 and separated the hospitalizations due to or with SLE using ICD 9 diagnostic codes previously established by HCUP. Among this population, we examined the patients with antiphospholipid antibodies (APLA) and compared their risk of seizures compared to the patients without APLA using the logistic regression model. The model was controlled for variables which included age, sex, race, ischemic stroke, intracranial bleed, hypertension, chronic kidney disease, uremia, lupus nephritis, lupus encephalitis, craniotomy, head trauma, hyponatremia, psychosis, intracranial infections, brain neoplasms, use of immunosuppression, alcohol use, abnormal electroencephalogram and use of antiepileptics. Using SAS 9.2, survey procedures were used to identify multivariate predictors of intractable epilepsy, grand mal status and epilepsia partialis continua. Results: A total of 1, 631, 680 hospitalizations with SLE were available for analysis of which 907 (0.06%) had intractable epilepsy, 2092 (0.13%) had grand mal status and 146 (0.01%) patients had epilpesia partialis continua. The odds ratio (OR) of intractable epilepsy in SLE patients with APLA was 1.157 (Confidence Interval (CI)=0.500-2.673, p value=0.7336); OR for grand mal status was 1.094 (CI=0.671-1.786, p value=0.7183); and OR for epilepsia partialis continua was 2.813 (CI=0.768-10.295, p value=0.1183). Conclusions: SLE and antiphospholipid antibody syndrome overlap significantly, and antiphospholipid antibodies are independently associated with increased risk of seizures. In our analysis, patients with SLE who have antiphospholipid antibodies were not at increased risk of having status epilepticus (partial or generalized). We also found that antiphospholipid antibodies are not an independent predictor for refractory epilepsy in patients with SLE. References: Herranz MT, Rivier G, Khamashta MA, Blaser, K U, Hughes GR (1994). Association between antiphospholipid antibodies and epilepsy in patients with systemic lupus erythematosus. Arthritis and Rheumatism, 37(4), 568-571. Disclosure of Interest: None declared